2010
DOI: 10.1371/journal.pone.0010084
|View full text |Cite
|
Sign up to set email alerts
|

Family and Population-Based Studies of Variation within the Ghrelin Receptor Locus in Relation to Measures of Obesity

Abstract: BackgroundThe growth hormone secretagogue receptor (GHSR) is mediating hunger sensation when stimulated by its natural ligand ghrelin. In the present study, we tested the hypothesis that common and rare variation in the GHSR locus are related to increased prevalence of obesity and overweight among Whites.Methodology/Principal FindingsIn a population-based study sample of 15,854 unrelated, middle-aged Danes, seven variants were genotyped to capture common variation in an 11 kbp region including GHSR. These were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
(23 reference statements)
0
12
2
1
Order By: Relevance
“…Co-segregation was seen for all obese individuals in the Czech pedigree; however two members of this pedigree were carriers of this mutation but not obese, possibly due to incomplete penetrance. The -151C/T mutation was subsequently genotyped in a population-based study of 15,854 Danish subjects; however in this study no association was found between the -151C/T mutation and obesity (Gjesing et al, 2010). …”
Section: Ghs-r Mutations In Patientsmentioning
confidence: 86%
See 1 more Smart Citation
“…Co-segregation was seen for all obese individuals in the Czech pedigree; however two members of this pedigree were carriers of this mutation but not obese, possibly due to incomplete penetrance. The -151C/T mutation was subsequently genotyped in a population-based study of 15,854 Danish subjects; however in this study no association was found between the -151C/T mutation and obesity (Gjesing et al, 2010). …”
Section: Ghs-r Mutations In Patientsmentioning
confidence: 86%
“…In addition, a A c c e p t e d M a n u s c r i p t 14 population-based study of 15,854 Danish subjects, in which seven common GHS-R SNPs were genotyped, failed to show association between the GHS-R variants and obesity (Gjesing et al, 2010). Further clinical studies are required to better define the frequency and the aetiological role of GHS-R isoforms in obesity ).…”
Section: Common Genetic Variations Of Ghrl and Ghs-r Genes In Human Omentioning
confidence: 99%
“…Although ghrelin is an orexigenic hormone primarily synthesized by X/A cells of the gastric mucosa, various attempts to relate genetic alterations of either ghrelin (5,6) or the GHSR (5,12,13,14,15) to body weight have yielded inconsistent results. Baessler et al (12) found that a disequilibrium block of five GHSR SNPs including rs572169 was associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Several large studies in various populations have investigated the effects of common GHSR variants on stature, weight, and body mass index (BMI) (4,5,12,13,14,15). Baessler et al (12) reported an association between GHSR variants and obesity; however, other studies have yielded negative results (5,13,14,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation